Caracterização química das folhas e avaliação in silico dos metabólitos isolados de Zanthoxylum caribaeum Lam (Rutaceae) - Andrade, Carine Raisa Barbosa de (2018)
Species of the genus Zanthoxylum (Rutaceae) present a very diversified and promising chemical composition, and it is frequently used in traditional medicine. The species Zanthoxylum caribaeum Lam. presents few studies that report its chemical and biological composition, which makes the species an excellent candidate for research aiming at the identification of molecules with biological potential. In this sense, the present work aimed to characterize the chemical composition of extracts and oil of the leaves of Z. caribaeum Lam. and to predict in silico new biological activities of the identified substances. The extracts were obtained by the maceration technique using methanol as solvent extractor. The chemical characterization was performed by previous phytochemical screening and fingerprintby HPLC-DAD of the extracts, as well as, the isolation, by means of chromatographic techniques and identification of secondary metabolites through spectroscopic and spectrometric techniques such as UV, MS and NMR of 1H and 13C.The oil was extracted by steam hydrodistillation and evaluated by GC- EM. The biological potential of the isolated molecules in the leaves of this species was verified by in silico techniques using methods based on the similarity of ligands (ChemProt 2.0 and SEA) and based on molecular target (DRAR-CPI). The chemical characterization showed that the extracts of the species in study presented a variety of secondary metabolites, such as phenolic compounds, tannins, flavonoids, coumarins, steroids / triterpenes and alkaloids by preliminary phytochemical tests. It was found by HPLC-DAD that the extracts are rich in phenolic compounds, particularly phenolic acids and flavonoids, it is possible to identify and quantify in the ethyl acetate extract of the substances rutin, trans-ferulic acid and caffeic acid.In the leaf extracts, 5 substances such as auraptenecoumarin, the mixture of phytosterols such as β-sitosterol and stigmasterol, sesamin lignan and hesperidinflavanone were isolated and identified. The essential oil gave a yield of 0.2%, with the presence of 20 components (91%), being linalool (27.72%), germacrene D (19.85%) and E-caryophyllene (14.45%) the major components.Among the selected molecular targets, auraptene targets the Beta secretase target and the endothelial protein C receptor; for the hesperidin the target Receptor activated by peroxisome proliferator gamma (PPARG), for sesamin, the nucleotide-binding histidine triad Protein 1, for the β-sitosterol targets the Estrogen Receptors and Protein tyrosine kinases (PTK) and for the stigmasterol the targets Estrogen Receptors and Arginine-Succinate Synthase (ASS). The prediction of in silico activities performed with the substances isolated and identified in the species allowed to raise potential targets for each compound. Thus, the results obtained contributed to a better knowledge of the chemical composition of Z caribaeum, besides providing unprecedented results for the species, the presence of different chemical classes and the isolation of substances already reported in the literature with potential biological activity, provide good perspectives of study with the species as a source of bioactive substances that could give rise to or serve as prototype models in the development of new pharmaceutical products.